Association Between the Reproductive Health of Young Women and Cardiovascular Disease in Later Life: Umbrella Review. Issue 3 (September 2021) - Okoth, K.; Chandan, J.S.; Marshall, T.; Thangaratinam, S.; Thomas, G.N.; Nirantharakumar, K.; Adderley, N.J.
Abstract : ( BMJ . 2020;371:1–21) One third of annual global deaths (17.9 million) can be attributed to cardiovascular disease (CVD). Risk factors for women include some outcomes related to pregnancy and fertility, however, these are often underrecognized. Hypertensive disorders of pregnancy, gestational diabetes mellitus, placental abruption, and low birth weight, and preterm births occur in up to one third of parous women in developed countries. Risk of CVD is also associated with early age at menarche/early menopause and use of hormonal contraceptive agents. This study aimed to conduct an umbrella review of systematic reviews to evaluate associations between female-specific risk factors (eg, adverse pregnancy outcomes and issues related to fertility) and CVD outcomes.